Variation in human genetic polymorphisms, their association with Helicobacter pylori acquisition and gastric cancer in a multi-ethnic country - Schmidt, Heather-Marie.A.; Ha, D.M.; Taylor, E.F.; Kovach, Z.; Goh, Khean-Lee; Fock, K.M.; Barrett, J.H.; Forman, D.; Mitchell, H. (Blackwell Publishing, 2010)
Background and Aim: The contribution of human genetic polymorphisms to Helicobacter pylori infection and gastric cancer (GC) development remains unclear due to geographic variation in the association between specific host genetic polymorphisms and GC. In the current study we investigated the association between polymorphisms related to immune and cancer-related pathways and H. pylori infection among the major ethnicities, Chinese, Malay and Indian, resident in Singapore and Malaysia as well as the association between these polymorphisms and GC development in ethnic Chinese patients.